2023
DOI: 10.1002/nafm.10837
|View full text |Cite
|
Sign up to set email alerts
|

Flow–recruitment relationships for Shoal Chub and implications for managing environmental flows

Abstract: ObjectiveRegulation of river flow regimes by dams and diversions impacts aquatic biota and ecosystems globally. However, our understanding of the ecological consequences of flow alteration and ecological benefits of flow restoration lags behind our ability to manipulate flows, and there is a need for broader development of flow–ecology relationships. Approaches for establishing flow–ecology relationships have recently shifted away from state‐based methods that analyze snapshots of ecological conditions and tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…However, potential for the conservation of species sensitive to flow regime alteration still exists (Liermann et al, 2012), particularly in locations where fragmentation and flow regime alterations are not coupled. Our data support the use of the blue sucker as a flow‐sensitive species that can be used to guide environmental flow decisions (Freeman et al, 2022), particularly in states such as Texas where ecological validation of flow regime standards is needed (Perkin et al, 2023). Specifically, our work informs management decisions by (1) reinforcing the need to protect riffle mesohabitats that are subject to the effects of flow alteration (Acre et al, 2021), (2) informing ecologically relevant values of habitat fragmentation and flow alteration that should be preserved or perhaps restored in regulated rivers (Wohl, 2017), and (3) providing quantitative descriptions for physical characteristic of rivers where repatriation efforts might be attempted in the future to reverse the pattern of decline for species such as blue sucker (Cathcart, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…However, potential for the conservation of species sensitive to flow regime alteration still exists (Liermann et al, 2012), particularly in locations where fragmentation and flow regime alterations are not coupled. Our data support the use of the blue sucker as a flow‐sensitive species that can be used to guide environmental flow decisions (Freeman et al, 2022), particularly in states such as Texas where ecological validation of flow regime standards is needed (Perkin et al, 2023). Specifically, our work informs management decisions by (1) reinforcing the need to protect riffle mesohabitats that are subject to the effects of flow alteration (Acre et al, 2021), (2) informing ecologically relevant values of habitat fragmentation and flow alteration that should be preserved or perhaps restored in regulated rivers (Wohl, 2017), and (3) providing quantitative descriptions for physical characteristic of rivers where repatriation efforts might be attempted in the future to reverse the pattern of decline for species such as blue sucker (Cathcart, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…We demonstrated how flow–ecology relationships can be used in predictive context by hindcasting the probability of occurrence across periods with historical flow records but only intermittent ecological data (see also Perkin et al. 2023, this special section). We found that probability of occurrence did not significantly change between 1950 to 1979 and 1980 to 2018, a finding that supports previous designation of the upper Brazos River as a refuge area for endemic Great Plains fishes (Hoagstrom et al.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Shoal Chub recruitment positively correlated with achievement of recommended flow pulses set by an expert science team in the lower Brazos River (Perkin et al. 2023), and Nguyen et al. (2021) provided similar flow targets for pelagic‐spawning fishes in the upper Brazos River.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We used total length data from all Silver Chub collected in the field (i.e., those retained for reproductive ecology research and those released) to fit a Bhattacharya model useful for estimating cohorts defined by modes within the length‐frequency histogram. We did not use otoliths to age fish because we were interested in using fish that were retained (otoliths available) and released (otoliths not available) for age estimates, though otoliths provide greater detail when aging (Perkin et al 2023; Wedgeworth et al 2023 [both this special section]). We used the “Bhattacharya” function from the “TropFishR” package to fit the model and develop probability density functions for each cohort detected in the data (Mildenberger et al 2017).…”
Section: Methodsmentioning
confidence: 99%